Boric acid and Schiff base-based fluorescent sensor for detection of L-tryptophan in milk and BSA samples - Kamaci, Umran Duru; Kamaci, Musa (Tubitak Scientific & Technological Research Council Turkey, 2022)
In the present paper, the fluorescence sensor based on Schiff base and boric acid was developed for easy and rapid detection of L-tryptophan in different samples such as milk and bovine serum albumin. The photoluminescence intensity was measured by using fluorescent measurements and the results indicated that the developed fluorescent sensor was exhibited selective, sensitive, reliable determination against L-tryptophan, and a series of various analytes such as cations, amino acids, and organic compounds were used to investigate the selectivity of the fluorescent chemosensor. The limit of detection and linear range of the chemosensor were calculated as 0.82 mu M, and 0.1-500 mu M, respectively. The performance of the chemosensor was evaluated in terms of selectivity, reversible usage, stability, and interference/anti-interference. The developed chemosensor was exhibited excellent photostability, and it was a great potential application of L-tryptophan in bovine serum albumin and milk samples.
Keywords: Tryptophan; boric acid; biosensor; fluorescent sensor; Schiff base; POLY(AZOMETHINE-URETHANE); AZOMETHINE; COMPOSITE; Chemistry; Engineering